Geschichten im digitalen Raum : Historisches Lernen in der „App in die Geschichte“ - Krebs, Alexandra (Medien der Geschichte, 2024)
In the age of digitality, the question is not so much whether learning about history is relevant in the digital space but how it should be modeled. In this volume, Alexandra Krebs develops a theoretical concept for such a model, which takes shape in her design of the digital learning platform "App in die Geschichte" (App into History). She also conducts an empirical inquiry into how learners use the app and how they collectively narrate history